MATHEMATICAL MODEL OF INCREASING THE RELIABILITY OF PRIMARY MEASUREMENT INFORMATION IN INFORMATION-CONTROL SYSTEMS - Ergashev Otabek Mirzapulatovich; Toychiboev Abbosjon Eralievich; Mamirkhodjaev Muhammadamin Mavlonjonovich (Galaxy International Interdisciplinary Research Journal, 2022)
In article mathematical model of the solution of problems of increase of reliability of primary measuring information systems are considered. It is shown what a problem of development of economically expedient complex of means of increase of reliability of information processing demands carrying out analysis in the form of the corresponding functional tasks, at the same time means of increase of reliability need to be divided into groups and levels of their interaction.